Renal failure in multiple myeloma: Incidence, correlations, and prognostic significance - Eleutherakis-Papaiakovou, V.; Bamias, A.; Gika, D.; Simeonidis, A.; Pouli, A.; Anagnostopoulos, A.; Michali, E.; Economopoulos, T.; Zervas, K.; Dimopoulos, M.A. (Leukemia and Lymphoma, 2007)
Renal failure (RF) is a common and severe complication of patients with multiple myeloma (MM). The purpose of our study was to assess the incidence of RF in a contemporary series of newly diagnosed patients with MM, its association with specific clinical and laboratory features, and its impact on patients' outcome. Over the last decade, 756 newly diagnosed symptomatic patients with MM were included in our database. Renal failure, defined as a serum creatinine ≥mg/dl at the time of diagnosis, was seen in 21% of patients. Multiple parameters were associated with RF, but logistic regression analysis showed that RF was independently associated only with International Staging System and Bence Jones proteinuria. The presence of RF was associated with a trend for higher early death rate but with a similar response to primary therapy. The median survival of patients with RF was 19.5 months versus 40.4 months for patients without RF (p < 0.001). Several variables were associated with impaired survival by univariate analysis. When multivariate analysis was performed the independent variables were poor performance status, thrombocytopenia, advanced age, high LDH and elevated serum β2 microglobulin but not high creatinine. When corrected for stage, renal failure had no impact on survival.